Pengaruh Faktor Makro Ekonomi dan Sektor Keuangan terhadap Permintaan Energi di Indonesia - Lilis Suryani; Siswoyo Hari Sentosa; Duwi Yunita Sari (UPT Penerbitan Universitas Jember, 2021)
Economic globalization has an impact on energy consumption caused by the macroeconomic sector and the financial sector. Macroeconomic indicators used in this study include GDP and FDI. GDP per capita is the level of annual income per capita based on a constant aggregate local currency based on a constant USD in 2010. FDI is net investment inflows consisting of total equity capital, reinvestment income, other long-term capital, and short-term capital as shown on the balance of payments. Whereas in the financial sector, the ratio of the amount outstanding is the total amount of money in the hands of the public and circulates in an economy to GDP. The trade stock ratio is the total shares traded on the stock exchange. Energy is the most important thing in the country's economy. The availability of energy must be sustainable to avoid an energy crisis in the future, it is necessary to have energy policies to regulate energy consumption. The method used to analyze the link to energy consumption in Indonesia is Ordinary Least Square (OLS) with time-series data from 1988-2017. The analysis shows that GDP and the ratio of the money supply have a significant influence on energy consumption in Indonesia, while FDI and the trade stock ratio do not have a positive and significant effect on energy consumption in Indonesia.